Single-step fabrication of 3D hierarchical ZnO/ZnS heterojunction branched nanowires by MOCVD for enhanced photoelectrochemical water splitting. Issue 17 (2nd March 2020) - Hassan, Mostafa Afifi; Waseem, Aadil; Johar, Muhammad Ali; Bagal, Indrajit V.; Ha, Jun-Seok; Ryu, Sang-Wan
Abstract : Rational design with a systematic and scalable single-step growth of 3D hierarchical ZnO/ZnS heterojunction branched NWs by MOCVD for enhanced photoelectrochemical water splitting efficiency. Abstract : We report a systematic and scalable single-step growth of three-dimensional hierarchical ZnO/ZnS heterojunction branched nanowires (3D ZnO/ZnS h-b-NWs) on a Si substrate using MOCVD for the first time and their application as photoanodes for photoelectrochemical water splitting (PEC-WS). Vertically well-aligned main trunk ZnO nanowires (MTr-ZnO NWs) were grown on a low-temperature ZnO buffer layer, which was followed by ZnS deposition. Subsequently, hierarchically branched ZnO nanowires (h-b-ZnO NWs) were grown on the side wall of the core–shell heterostructure, which was further modified with a thin layer of ZnS for the growth of multiple ZnO NW branches. The PEC-WS results revealed that the photo-conversion efficiency achieved using MTr-ZnO NWs and 3D ZnO/ZnS h-b-NWs was 0.03% and 0.46% at 0.5 V vs. RHE, respectively, which corresponds to 16-fold enhancement. The achieved improvements can be attributed to the enhanced photoabsorption, which is directly related to the augmented surface area. In addition, ZnS plays a significant role in promoting faster photogenerated carrier transport with high efficiency and visible light absorption by type-II transition at the ZnO/ZnS interface. The novel growth approach that we followed to fabricate the photoanode opens a new avenue for the synthesis of multiple-level hierarchical heterostructures that are beneficial for PEC-WS devices.